2005
DOI: 10.1080/07924259.2005.9652180
|View full text |Cite
|
Sign up to set email alerts
|

The reproductive cycle ofPatella candei gomesiiDrouët, 1858 (Mollusca: Patellogastropoda), an Azorean endemic subspecies

Abstract: SummaryPatella candei gomesii is morphologically plastic comprising two ecomorphs. The "smooth limpet" is characteristic of the eulittoral zone, whereas the "fly limpet" is mainly found higher in the shore, on the splash zone of exposed areas. Their reproductive strategies are poorly understood. This study investigated the reproductive cycles of the ecomorphs using histological techniques. The annual cycles were found to be similar. Both sexes exhibited synchronous patterns and were mature most of the year. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Four stages of spermatogenesis were identified, based on the classification of Griffond et al (1991) and Curdia et al (2005): (1) spermatogonia, medium-sized cells rectangular in shape when viewed by light microscopy, with a large nucleus in relation to the quantity of cytoplasm, always located near the acinus epithelium; (2) spermatocytes, smaller than spermatogonia with basophilic cytoplasm; (3) spermatids, smaller than spermatocytes, spheroidal in shape and slightly more basophilic than spermatocytes; (4) spermatozoa -with strong basophilic heads and eosinophilic tails. Spermatocytes I and II could not be distinguished from each other.…”
Section: Methodsmentioning
confidence: 99%
“…Four stages of spermatogenesis were identified, based on the classification of Griffond et al (1991) and Curdia et al (2005): (1) spermatogonia, medium-sized cells rectangular in shape when viewed by light microscopy, with a large nucleus in relation to the quantity of cytoplasm, always located near the acinus epithelium; (2) spermatocytes, smaller than spermatogonia with basophilic cytoplasm; (3) spermatids, smaller than spermatocytes, spheroidal in shape and slightly more basophilic than spermatocytes; (4) spermatozoa -with strong basophilic heads and eosinophilic tails. Spermatocytes I and II could not be distinguished from each other.…”
Section: Methodsmentioning
confidence: 99%
“…However, this was evident in both LPZs and SCAs suggesting that this was not the result of fishing closed seasons per se. Although P. candei can spawn throughout the year (Martins et al, 1987), recent work has shown that there is a peak spawning event occurring in late summer (Cúrdia et al, 2005). Hence, the greater abundance of limpets by the end of the closed harvesting season was probably the result of previous recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…gomesii, a common intertidal subspecies of the Azores (Hawkins et al 1990;Weber and Hawkins 2002), is heavily exploited for consumption and its fishery collapsed in 1988 (Ferraz et al 2001). The species exhibits two eco-morphs with variations in the shell sculpture which are thought to depend on the substrate and exposure to wave action (Hawkins et al, 1990), although genetic (Pagarete et al, 2005) and histological (Cúrdia et al, 2005) evidence support the conspecificity of these eco-morphs. Cúrdia et al (2005) have shown that while P.c.…”
mentioning
confidence: 99%
“…The species exhibits two eco-morphs with variations in the shell sculpture which are thought to depend on the substrate and exposure to wave action (Hawkins et al, 1990), although genetic (Pagarete et al, 2005) and histological (Cúrdia et al, 2005) evidence support the conspecificity of these eco-morphs. Cúrdia et al (2005) have shown that while P.c. gomesii is able to spawn throughout the year, there is a major spawning event during summer, with synchrony of genders.…”
mentioning
confidence: 99%
See 1 more Smart Citation